(untitled) (Nepal Journal of Epidemiology, 2014)
Background Nepalese population includes a wide variety of ethnic groups namely, the Brahmin, Chettri, Dalit, Gurung, Newar, Puns, Magar Dalits population in Nepal are a traditionally victimised, underprivileged community who have been obliged to lag at the base of the public constitution in Nepal. Dalits Nepalese has poor income, education and other human development indicators. They are often landless and much poorer than the dominant caste population like the Brahmins, chetris, newars. The main objective of the study was to find out the commonest psychiatric disorder found in the poor Dalit Nepalese population in western development region of Nepal for which hospitalization is required. Method The study was a cross sectional study carried out between 1st October- 31st March 2010 at Psychiatric ward in Manipal Teaching hospital. The diagnosis of the disease was based on ICD-10 (Tenth revision) Classification of mental and behavioral disorders, Diagnostic Criteria for Research.. Results Among all the psychiatric diseases Schizophrenia, Schizotypal and Delusion Disorders 30.6% was the commonest disease seen in the Dalit Population followed by Mental and behavioral disorder due to Psychoactive Substance abuse 20.8%. Psychiatric diseases were more common in male patients 52.8%. 87.5% of the cases were <40 yrs of age, 72.2% of the patients were Hindus by religion followed by Christian 27.8%. 87.5% of the patients were unemployed and 84.7% of the patients were having monthly income <10000/month. 45.8% of the patients were students followed by housewife 34.7%. Mental and behavioural disorder due to Psychoactive Substance abuse F10-19 was found more prevalent in males [OR 8.320,95%(CI(1.717, 40.311)] as compared to female patients among the Dalit patients Conclusion Among the low socio-economic class Dalits Schizophrenia was the commonest psychiatric disorder followed by Mental and behavioral disorder due to Psychoactive Substance abuse. Psychiatric illnesses are mediated by poverty, unemployment and dearth of family income which leads to psychiatric illness among dalit Nepalese population. Interventions should target these factors to minimise the load of various psychiatric illness among poor Dalit Nepalese population. DOI: http://dx.doi.org/10.3126/nje.v4i3.10667 Nepal Journal of Epidemiology 2014; 4(3): 370-377